Spatial variability of soil physical attributes in integrated production systems in the Amazon region - Feitosa, Izabela de Lima; Passos, Alexandre Martins Abdão dos; Cipriani, Henrique Nery; Oliveira, Marcelo Silva de; Marcolan, Alaerto Luiz; Vasques, Gustavo Mattos (Pesquisa Agropecuaria Brasileira, 2019)
The objective of this work was to analyze the spatial variability of soil physical attributes in integrated production systems and its relationship with the growth and yield of a corn (Zea mays) crop intercropped with palisade grass (Urochloa brizantha). The experiment was carried out in an integrated crop-livestock (ICL) system and in an integrated crop-livestock-forestry (ICLF) system, in a Typic Hapludox. The ICLF system was managed in alleys between eucalyptus (Eucalyptus spp.) rows, spaced at 18, 30, and 42 m. Corn grain and forage yields were positively correlated with soil clay and moisture contents, whereas grain yield was negatively correlated with soil penetration resistance. The lowest corn plant heights and grain yields were observed near eucalyptus rows. The average values for soil penetration resistance were below 2.0 MPa. Spatial variability was verified for: corn plant height, grain yield, and agronomic efficiency; forage intercropping; and soil moisture and silt contents, as well as penetration resistance. Greater grain and biomass yields were obtained at a 42-m distance between tree rows. The obtained results are indicative that corn traits and soil physical attributes were only slightly associated. The spatial distribution of the eucalyptus rows influences the agronomic efficiency of the intercrop and soil moisture contents.